2011
DOI: 10.1186/1475-2875-10-132
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous decrease in malaria prevalence in children over a six-year period in south-western Uganda

Abstract: BackgroundMalaria is a major public health problem, especially for children. However, recent reports suggest a decline in the malaria burden. The aim of this study was to assess the change in the prevalence of malaria infection among children below five years of age between 2004 and 2010 in a mesoendemic area of Uganda and to analyse the risk factors of malaria infection.MethodsTwo cross-sectional surveys were conducted in 2004 and in 2010 at the end of the rainy and dry seasons to measure the prevalence of P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
62
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 27 publications
6
62
0
Order By: Relevance
“…Despite a decrease in malaria prevalence in the area during the study 6 , cerebral malaria was the main aetiology in our cohort, followed by bacterial meningitis. Although we investigated a large range of viruses, we found few viral infections, most of which were in children co-infected with another pathogen.…”
Section: Discussionmentioning
confidence: 62%
“…Despite a decrease in malaria prevalence in the area during the study 6 , cerebral malaria was the main aetiology in our cohort, followed by bacterial meningitis. Although we investigated a large range of viruses, we found few viral infections, most of which were in children co-infected with another pathogen.…”
Section: Discussionmentioning
confidence: 62%
“…The younger children were also significantly more likely to sleep under ITNs compared to those aged from five to 13 years [31]. Similar trends were found in both rural and urban areas in Uganda [19]. …”
Section: Discussionmentioning
confidence: 83%
“…Previous studies reported a decline in malaria prevalence in febrile children over time [4,14,18,19]. In Mlomp, Senegal, an area of moderate malaria transmission, the risk of malaria decreased by about 32 times between 1996 and 2010, including the control strategy implementation period [18].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study in Western Kenya reported a malaria prevalence of 82.5% in hospitalized children [19]. Other recent studies however, have reported declining prevalence of malaria attributed to interventions to prevent and/or treat malaria [6], [20], [21].…”
Section: Discussionmentioning
confidence: 99%